Research on Wideband Differential-Mode Current Injection Testing Technique Based on Directional Coupling Device - Xiaodong Pan; Guanghui Wei; Xinfu Lu; Lisi Fan; Xing Zhou (International Journal of Antennas and Propagation)
This paper presents a new kind of differential-mode current injection test method. The equal response voltage on the cable or the antenna port of the equipment under test (EUT) is regarded as equivalent principle for radiation and injection test. The injection and radiation response analysis model and the injection voltage source extrapolation model in high intensity radiated field are established. The conditions of using differential-mode current injection as a substitute for radiation are confirmed. On the basis of the theoretical analysis, the function and structure design scheme of the directional coupling device is proposed. The implementation techniques for the single differential-mode current injection method (SDMCI) and the double differential-mode current injection method (DDMCI) are discussed in detail. The typical nonlinear response interconnected systems are selected as the EUT. The test results verify the validity of the SDMCI and DDMCI test methods.